PENGARUH INTERVAL PEMBERIAN AIR KELAPA DAN PUPUK UREATERHADAP PERTUMBUHAN BIBIT KARET(Heveea brasiliensis) STUM MATA TIDUR - Agung cahyo saputro; Elza Zuhry (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the effect of interval of coconut water and the dose of Nitrogen fertilizer on the growth of rubber eye stool grafting seeds and get the best treatment on the growth of rubber eye stool rubber seeds. This research was conducted in experimental garden of Agricultural Faculty of Universitas Riau, Tampan, Pekanbaru in June 2016 until August 2016. The experiment was conducted experimentally by using Factorial Random Design (RAL) consisting of 2 factors, the first factor consisted of 2 interval levels (cc / L) ie 3 days and 6 days and second factor: Nitrogen fertilizer with 4 dosage (g / plant) ie 3 g / plant, 6 g / plant, 9 g /. The data obtained were analyzed using Duncan's multiple-range test at 5% level. Interval of young coconut water and dose of urea fertilizer give significant effect to shoot diameter, shoot length, leaf number and leaf rubber seed stum, but not significant effect on shoot growth time. Provision of young coconut water at intervals of 3 days and dose of urea 9 g / plant fertilizer, can produce bud diameter, leaf number and leaf area.Keywords: Coconut Water Interval, Urea Fertilizer, Growth and Development of rubber seedlings.